2009
DOI: 10.1111/j.1740-8261.2009.01568.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Fish Gender Using Fractal Analysis of Ultrasound Images

Abstract: The gender of cod Gadus morhua can be determined by considering the complexity in their gonadal ultrasonographic appearance. The fractal dimension (D(B)) can be used to describe this feature in images. B-mode gonadal ultrasound images in 32 cod, where gender was known, were collected. Fractal analysis was performed on these images and D(B) was determined using the box counting method. A receiver-operating curve (ROC) was drawn for D(B) as a test for male fish. Using a range of D(B) values, the maximum accuracy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…), and 78% of adult Atlantic Cod Gadus morhua (McEvoy et al. ). However, for species like the Red Hind Epinephelus guttatus , gonads can be identified only immediately prior to spawning (Whiteman et al.…”
Section: Discussionmentioning
confidence: 99%
“…), and 78% of adult Atlantic Cod Gadus morhua (McEvoy et al. ). However, for species like the Red Hind Epinephelus guttatus , gonads can be identified only immediately prior to spawning (Whiteman et al.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual dimorphism is a phenomenon in which fish exhibit distinct external characteristics between males and females [4][5][6]. Sex identification is a fundamental study in fish biology and aquaculture, and its results provide a theoretical basis for precious fish conservation and artificial reproduction [7]. Studies have found that many species of female and male fish show more pronounced differences in body size, minority body structure, and body surface color [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In the same way, since early 1980s, ultrasonography has been mainly used to determine the sex of numerous fish species, for conservation, research or aquaculture purposes. Among them, we can list coho salmon Oncorhynchus kisutch (Martin et al, 1983), Pacific herring Clupea pallasii (Bonar et al, 1989), Atlantic salmon Salmo salar (Mattson, 1991;Naeve et al, 2018), rainbow trout Oncorhynchus mykiss (Reimers et al, 1987), Atlantic halibut Hippoglossus hippoglossus (Martin-Robichaud & Rommens, 2001;Shields et al, 1993), striped bass Morone saxatilis (Blythe et al, 1994), Atlantic cod Gadus morhua (Karlsen & Holm, 1994;McEvoy et al, 2009), stellate sturgeon Acipenser stellatus (Moghim et al, 2002), shovelnose sturgeon Scaphirhynchus platorynchus (Colombo et al, 2004;Wildhaber et al, 2005), Murray cod Maccullochella peelii peelii (Newman et al, 2008), hapuku Polyprion oxygeneois (Kohn et al, 2013), European eel Anguilla Anguilla (Kucharczyk et al, 2016) or Chinese sturgeon Acipenser sinensis (Du et al, 2016).…”
Section: Introductionmentioning
confidence: 99%